Socio-environmental factors and depression among secondary school children in Dhaka city (Bangladesh Journal of Psychiatry, 2018)
Depression among children and adolescents has been increasingly recognized as a major public health problem. The objective of the study was to find out socio-environmental factors associated with the presence of depression among secondary school children in Dhaka city. It was a cross-sectional study conducted from November 2008 to October 2009 in two purposively selected schools (one boys’ and one girls’) of Dhaka city. Simple random sampling was used to collect 144 samples from class VI to class IX. A semi-structured self-administered questionnaire including the translated Bangla version of the Center for Epidemiologic Studies Depression Scale for Children (CES-DC) was used to assess depression. The results showed that, majority of the respondents lived in nuclear family whereas 79.2% boys and 51.4% girls had only 1-2 siblings. The mean number of siblings (2.19+0.588) was higher among the respondents with depression than among the respondents without depression which was statistically significant. In boys’ school, emotional bullying by peer group was complained mostly by the students of class VIII (22.2%) whereas in girls’ school, students of class VI (44.4%) complained of being bullied emotionally mostly. In this study, those boys (45.5%) who complained of emotional bullying by their peer group were found as significantly depressed than those who had no such complaints. Proportion of depression was higher among those respondents who had any history of physical or psychiatric illness in their family. The findings of the study emphasized on the importance of the school mental health services.Bang J Psychiatry December 2015; 29(2): 48-52